Analysis of the Effect and Role of Indoor Environmental Quality in the COVID-19 Transmission - Katharina Oginawati; Rinaldy Jose Nathanael; Udjianna Sekteria Pasaribu; Utriweni Mukhaiyar; Afif Humam; Nisa Fadlilah Fathul Ilmi; Septian Hadi Susetyo (Aerosol and Air Quality Research)
Abstract Infectious diseases such as COVID-19 have some risk factors. One of the most important factors is the environment. This research focused on risk factors concerning the house environment. This study aimed to evaluate the parameters of the ‘healthy house’ environment in controlling the spread of COVID-19. This study used environmental quality, namely ventilation, humidity, brightness, temperature, and personal space area as house environment parameters. The location of the study is Coblong District, Bandung City. The χ2 test of independence was used to show the significance between environmental parameters required for the healthy house and disease transmission. The study found that one house environment parameter (ventilation) are significantly related to indoor transmission rate in recovered patients’ houses (p = 0.021). Pearson correlation coefficient r was also investigated for each element of environment factor on the indoor transmission rate. Ventilation was found to be the most significant parameter correlated with indoor transmission (r = −0.522, p = 0.002). Personal Space Area also observed to have a significant correlation with indoor transmission rate (r = 0.459, p = 0.008). Humidity, brightness, and temperature were observed to have no significant correlation with indoor transmission rate (p = 0.309, 0.735, and 0.953, respectively. Linear regression is used to further investigate and predict the indoor transmission rate with significant environmental parameter as predictor. The linear regression model showed that 27.3% of indoor transmission rate variability are caused by its relationship with ventilation, the predictor used in the model.